A hypothesis about the role of fetal hemoglobin in COVID-19 (2020)
COVID-19 infection is less common in children (with higher fetal hemoglobin levels). In our preliminary study, we also observed a low prevalence and fatality of COVID-19 in countries with high rate of hemoglobinopathy carries. Given these two facts, the hemoglobin structure can play a role in the physiopathology of COVID19 disease. Several drugs are known to increase fetal hemoglobin in adults. Adding these drugs to COVID-19 clinical trials may improve the patients’ outcomes.